Analysing Pedagogic Discourse through the Teachers' Use of Space in EFL Classrooms - Satrio Aji Pramono (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2023)
In language classrooms, the use of space has the same potential as language in shaping the pedagogical process. This study analyzes different types of classroom space and how they are used by two teachers to make different meanings. The analysis was carried out by focusing on the positioning of the teachers during lesson stages, namely Openings, Sequencing, and Closings based on the semantic categories of classroom space developed by Lim et al. (2012). The results explicated the use of four different types of space, namely authoritative space, personal space, supervisory space, and interactional space to create learning experience and how they are redefined by the teachers for specific reasons. The findings of this study are expected to provide insight as to how classroom space as one of the semiotic resources is crucial to the pedagogical process and therefore offers a way for teachers to evaluate and transform how they approach their teaching.